Sistem Pendukung Keputusan Penilaian Kompetensi Guru Menggunakan Metode Analytical Hierarki Process - Aimede Primackof Pouryono; Intan Purnamasari; Bagja Nugraha (Jurnal Ilmiah Informatika, 2020)
Junior High School 3 Patokbeusi is one of the schools that implements Teacher Competency Assessment one by one for the school year. In the assessment, the problem that is often an obstacle is the assessment process which is very complicated if it has to be done manually and the possibility of errors in calculating the value and recapping the value is more vulnerable. This is what makes the Teacher Competency Assessment process ineffective and inefficient. Based on the problems that have been described, it is necessary to make a solution to overcome the problems of Teacher Competency Assessment by making a web-based system application using the Analitycal Hierarchy Process (AHP) method. The process of determining this ranking uses the weights of the 14 criteria tested and is used to determine the highest alternative assessment value or the highest teacher competency value based on 14 pre-determined criteria weights. In this decision support system, it produces a value that is used as a problem-solving tool in determining the best performing teacher which has been done manually by the school. The results of this thesis research produce a web-based teacher competency assessment decision support system. Then to test this program, the authors use blackbox testing, whitebox testing and questionnaires where this questionnaire is a form filling stage by teachers and friends to assess the feasibility level of this program where the results of filling out the questionnaire form produce an overall score above 75. and is included in the “Very Good” rating, so it can be concluded that the teacher competency assessment decision support system program is worthy of being used as a process to determine the best teacher.